The Role of Investigative Television Programs in Public Awareness in The Kurdistan Region: (The issue of social peace), for example - Asst. Prof. Rebar Goran Mustafa; Halat Jaafer Khurseed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
After the spring uprising of 1991, the media environment witnessed a new phase in publishing newspapers and magazines in a free nature and broadcasting their own radio and television. This freedom in the Kurdistan Region led the Kurdish media to an advanced stage in terms of quantity, but in that it was not without problems, an attempt was made to provide freedom for journalists from here or there so that they could criticize the shortcomings in Kurdish society, as well as the investigation not only that Rather, programs should be prepared and presented to establish television screens and present them as a start to media work in a new media type. Therefore, the existence of a basic program that is definitely related to the political situation and the regional system of government in the aspects of administrative issues and the state’s control over the conditions of society in rehabilitating the reconciliation and peace of society, as well as the problems in which countries where freedom grieves are criticized. Journalists are not allowed to work freely and present their programmes.